2014
DOI: 10.1016/j.contraception.2013.10.018
|View full text |Cite
|
Sign up to set email alerts
|

A two-pill sublingual misoprostol outpatient regimen following mifepristone for medical abortion through 70 days' LMP: a prospective comparative open-label trial

Abstract: A regimen of 200 mg mifepristone followed in 24-48 h by 400 mcg sublingual misoprostol is effective up to 70 days' LMP. The findings have important implications for expanding access to outpatient medical abortion services in settings where the cost of misoprostol is of concern or a two-pill misoprostol regimen is the standard of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 19 publications
2
27
1
Order By: Relevance
“…A study comparing the efficacy of two pill sublingual misoprostol outpatient regimen through 70 days GA reported the success rate of 94.8% in the 57-63 days group. 12 This two pill regimen opens up possibility of further research with low dose misoprostol in our set up as well. The lower success rate in our study could be because of smaller sample size.…”
Section: Safety Efficacy and Acceptability Of Early First Trimester mentioning
confidence: 85%
“…A study comparing the efficacy of two pill sublingual misoprostol outpatient regimen through 70 days GA reported the success rate of 94.8% in the 57-63 days group. 12 This two pill regimen opens up possibility of further research with low dose misoprostol in our set up as well. The lower success rate in our study could be because of smaller sample size.…”
Section: Safety Efficacy and Acceptability Of Early First Trimester mentioning
confidence: 85%
“…Increased availability of medical abortion is attributed to declines in mortality and morbidity of unsafe abortion [19]. Medical abortion with evidence-based mifepristone and misoprostol protocols is safe and effective for pregnancy termination up to 70 days gestation [20][21][22][23][24]. A 2015 retrospective cohort study including over 30,000 women undergoing early abortion found similar efficacy and low complication rates when comparing surgical abortion with medical abortion [25].…”
Section: Introductionmentioning
confidence: 93%
“…111 A study from Gynuity Health involving 729 women undergoing termination of pregnancy showed efficacy of this regimen up to 70 days gestation. 112 Recent guidelines jointly distributed by ACOG and the Society of Family Planning claim that evidence-based protocols are superior to the FDA-approved regimen. 113 According to the guidelines, most women are candidates for medical abortion.…”
Section: Medical Abortionmentioning
confidence: 99%